Current Strategies of Antiviral Drug Discovery for COVID-19 - Mei, Miao; Tan, Xu (Frontiers in Molecular Biosciences, 2021)
SARS-CoV-2 belongs to the family of enveloped, single-strand RNA viruses known as betacorovirues in Coronaviridae, first reported late 2019 in China. It has since been circulating world-wide, causing the COVID-19 epidemic with high infectivity and fatality rates. As of the beginning of April 2021end of February 2020, pandemic SARS-CoV-2 has infected more than 100 130 million people and led to more than 2.84 million deaths. Given the severity of the epidemic, scientists from academia and industry are rushing to identify antiviral strategies to combat the disease. There are several strategies in antiviral drugs for coronaviruses including empirical testing of known antiviral drugs, large-scale phenotypic screening of compound libraries and target-based drug discovery. To date, an increasing number of drugs have been shown to have anti-coronavirus activities in vitro and in vivo, but only rRemdesivir and several neutralizing antibodies has have been approved by the US FDA for treating COVID-19. However, remdesivir’s clinical effects are controversial and new antiviral drugs are still urgently needed. We will discuss the current status of the drug discovery efforts against COVID-19 and potential future directions.